2012
DOI: 10.5688/ajpe76470
|View full text |Cite
|
Sign up to set email alerts
|

A Spanish Language Module in a First-Year Pharmaceutical Care Laboratory Course

Abstract: Objective. To assess the impact of incorporating Spanish language lectures and activities in a required Pharmaceutical Care Laboratory course on first-year doctor of pharmacy (PharmD) students' perceptions of and comfort level with Spanish-speaking patients and basic knowledge of Spanish pharmacy terms. Design. The 6-week module consisted of attendance at a 1-hour lecture on medical Spanish and Hispanic culture, and completion of 4 small-group activities: drug and product information, patient information, coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…There are numerous accounts of other healthcare disciplines are responding to the need for Spanish-speaking providers with courses furthering students' understanding of Spanishlanguage terminology (Bender, Lawson, Harlan, & Lopez, 2004;Bloom, Timmerman, & Sands, 2006;Cobb, Perez-Brown, and Owens, 2011;Dinkins & Scolaro, 2012;Mazor, Hampers, Chande, & Krug, 2002). Mental health professionals have been one group of healthcare professionals that has used "ethnic matching" to pair Hispanic/Latino patients with bilingual providers (Castaño, Biever, González, & Anderson, 2007;Verdinelli & Biever, 2009).…”
Section: Profession-specific Vocabulary Training Of Studentsmentioning
confidence: 99%
“…There are numerous accounts of other healthcare disciplines are responding to the need for Spanish-speaking providers with courses furthering students' understanding of Spanishlanguage terminology (Bender, Lawson, Harlan, & Lopez, 2004;Bloom, Timmerman, & Sands, 2006;Cobb, Perez-Brown, and Owens, 2011;Dinkins & Scolaro, 2012;Mazor, Hampers, Chande, & Krug, 2002). Mental health professionals have been one group of healthcare professionals that has used "ethnic matching" to pair Hispanic/Latino patients with bilingual providers (Castaño, Biever, González, & Anderson, 2007;Verdinelli & Biever, 2009).…”
Section: Profession-specific Vocabulary Training Of Studentsmentioning
confidence: 99%
“…Currently, there is a very small body of literature regarding Medical Spanish being taught in healthcare curricula throughout the U.S. Besides pharmacy schools, 3,4 Medical Spanish courses have been described in the literature for medical, 5,6 physical therapy, 7 physician assistant (PA), 8 and nursing schools. 9 Reuland and colleagues discussed the impact of immersion rotations on medical student Spanish fluency and found that medical students that had an intermediate to high baseline in Spanish fluency were more likely to increase their skill set as compared to those that did not have this experience.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed information on Medical Spanish education for the pharmacy practice-specific setting is limited to case reports of mission trips, lectures, courses, and an outreach event. 3,4,[11][12][13][14] By understanding methods and strategies used by other institutions, the first step of the innovation process will be complete. To that end, this study was designed to determine characteristics of Medical Spanish education to pharmacy students in schools and colleges of pharmacy in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…To produce graduates capable of the linguistically competent care that is championed in the aforementioned documents, many health professions educators have developed relevant training. Reflecting the predominance of people with LEP who speak Spanish (MPI, 2011), many curricula from institutions across the country include Spanish language training (Bloom, Timmerman, & Sands, 2006; Dinkins & Scolaro, 2012; Frasier, Davalos, & Nusbaum, 2005; Lusk, Chavez Baray, Palomo, & Palacios, 2014; Masin & Tischenko, 2007; Pechak, Diaz, & Dillon, 2014; Reuland, Frasier, Slatt, & Aleman, 2008; Reuland, Slatt, Aleman, Fernandez, & DeWalt, 2012; VanTyle, Kennedy, Vance, & Hancock, 2011). These models range from offering elective Spanish training opportunities (Lusk et al, 2014; Masin & Tischenko, 2007; Reuland et al, 2008; Reuland et al, 2012; VanTyle et al, 2011) to requiring students to participate in Spanish training (Bloom et al, 2012; Dinkins & Scolaro, 2012; Frasier et al, 2005; Pechak et al, 2014).…”
mentioning
confidence: 99%
“…Reflecting the predominance of people with LEP who speak Spanish (MPI, 2011), many curricula from institutions across the country include Spanish language training (Bloom, Timmerman, & Sands, 2006; Dinkins & Scolaro, 2012; Frasier, Davalos, & Nusbaum, 2005; Lusk, Chavez Baray, Palomo, & Palacios, 2014; Masin & Tischenko, 2007; Pechak, Diaz, & Dillon, 2014; Reuland, Frasier, Slatt, & Aleman, 2008; Reuland, Slatt, Aleman, Fernandez, & DeWalt, 2012; VanTyle, Kennedy, Vance, & Hancock, 2011). These models range from offering elective Spanish training opportunities (Lusk et al, 2014; Masin & Tischenko, 2007; Reuland et al, 2008; Reuland et al, 2012; VanTyle et al, 2011) to requiring students to participate in Spanish training (Bloom et al, 2012; Dinkins & Scolaro, 2012; Frasier et al, 2005; Pechak et al, 2014). They also vary from offering a single Spanish course (Bloom et al, 2012; Dinkins & Scolaro, 2012; Frasier et al, 2005; Masin & Tischenko, 2007) to multiple, targeted opportunities to practice Spanish, incorporating role-playing in clinical courses and service-learning/clinical education experiences with Spanish-speaking individuals with LEP (Lusk et al, 2014; Pechak et al, 2014; Reuland et al, 2008; Reuland et al, 2012; VanTyle et al, 2011).…”
mentioning
confidence: 99%